2013
DOI: 10.1155/2013/850193
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol in Use for Treatment of Complex Infant Hemangiomas: Literature Review Regarding Current Guidelines for Preassessment and Standards of Care before Initiation of Therapy

Abstract: In 2008, the positive effects of propranolol on infantile hemangiomas (IH) have been discovered serendipitously by Léauté-Labrèze and her coworkers. Since then, propranolol has been in use in allday clinical practice worldwide for treatment of IH. It even caused some kind of paradigm shift in the overall management of these lesions, though propranolol is still not FDA approved, respectively, in “off-label” use for this indication in the majority of institutions. Thus, the aim of this communication is to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 70 publications
0
17
0
5
Order By: Relevance
“…The use of propranolol, the well‐known antihypertensive medication, has been serendipitously noted to control the growth of hemangiomas by Léauté‐Labrèze and her coworkers in 2008 in a large‐scale placebo‐controlled randomized clinical study while being in use for treatment of (congenital) heart disease in French children . As a consequence, oral propranolol has become the first‐line therapy for the treatment of hemangiomas for its efficacy and safety .…”
Section: Discussionmentioning
confidence: 99%
“…The use of propranolol, the well‐known antihypertensive medication, has been serendipitously noted to control the growth of hemangiomas by Léauté‐Labrèze and her coworkers in 2008 in a large‐scale placebo‐controlled randomized clinical study while being in use for treatment of (congenital) heart disease in French children . As a consequence, oral propranolol has become the first‐line therapy for the treatment of hemangiomas for its efficacy and safety .…”
Section: Discussionmentioning
confidence: 99%
“…The phase 2/3 dose ranging study has demonstrated the efficacy and tolerability of the new pediatric solution of propranolol at the dose of 3 mg kg −1 day −1 given BID. However, the available literature on the treatment of IH largely documented TID dosing regimen . Considering that repeated administration of treatment in infants could not always be a regular dosing regimen (due to possible irregular sleeping periods and meal times), irregular BID dosing regimen and 2 different TID dosing regimens were simulated and compared with the regular BID dosing regimen investigated in the clinical PK study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the available literature on the treatment of IH largely documented TID dosing regimen. 11,13,16,42 Considering that repeated administration of treatment in infants could not always be a regular dosing regimen (due to possible irregular sleeping periods and meal times), irregular BID dosing regimen and 2 different TID dosing regimens were simulated and compared with the regular BID dosing regimen investigated in the clinical PK study. Whatever the dosing regimen, simulations confirmed that infants are exposed to propranolol over a 24 hour-period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical studies have demonstrated new therapeutic indications with lower concentrations of propranolol, as in the treatment of infantile hemangiomas (19), burned patients (20), and posttraumatic stress disorder (21), although further research is required to confirm these findings.…”
Section: Introductionmentioning
confidence: 99%